Analysis of WISPR Images of the Near-Sun Heliospheric Current Sheet Region from Parker Solar Probe Encounters 4 and 5 and Comparison with the in Situ Observations - Paulett C. Liewer; Samuel T. Badman; Mark Linton; T. D. Phan; Guillermo Stenborg; Angelos Vourlidas (The Astrophysical Journal)
We present an analysis of Wide-field Imager for Solar PRobe (WISPR) images of the near-Sun heliospheric current sheet (HCS) region from the Parker Solar Probe (PSP) in 2020 January and June. Previous analysis of the solar wind data from PSP’s in situ instruments for these periods has shown multiple signatures of magnetic reconnection during HCS encounters. The signatures, including field line disconnections, density enhancements, and reconnection flows, indicated that reconnection was nearly always active in the HCS near the Sun. Here, we present an analysis of WISPR white-light observations of the HCS region during the same time periods, using an image-processing technique that enhances changes in the images from frame to frame. This processing reveals the presence of a nearly continual stream of transient density enhancements (“blobs”) within the helmet streamer flow not evident in the standard calibrated-brightness images. The blobs, observed frequently in the helmet streamer flows by white-light imagers, are broadly interpreted as resulting from reconnection in the vicinity of the HCS. Thus, the WISPR observations are consistent with the in situ data finding that reconnection is almost always active in the HCS near the Sun. We use the Tracking and Fitting technique to determine the trajectory and size of a few of the more distinct blobs. We confirm that the blobs lie near the HCS and find that the sizes of the imaged blobs are similar to the size estimates for possible blobs seen in situ in the HCS at similar distances from the Sun.